2022
DOI: 10.4038/jccpsl.v27i5.8435
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer burden in Sri Lanka- 2005 to 2019: does it differ with site and sex?

Abstract: Introduction: Oral cancer is the commonest cancer among Sri Lankan males for decades.Objectives: To describe the sex difference in site specific cancers in oral cavity and to analyse the incidence trends according to sex, sites and age category of oral cancer in Sri Lanka between 2005 and 2019 Methods: Data on oral cancers were obtained from National Cancer Registry, Sri Lanka (NCR-SL) from 2005 to 2019. Sex difference for lip, tongue and mouth cancers were analysed. Analysis was performed with Joinpoint Trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These findings have been corroborated by a recent study including data obtained from National Cancer Registry of Sri Lanka, as well as raw data possessed by National Cancer Control Programme for the period from 2005 to 2019. This study showed a rising trend in age standardized incidence rates, of oral cancer over the past two decades both in males and females 34 . Among males, the proportional increase in age standardized incidence rates rose from 9.8 to 19.1 per 100 000 population from 2005 to 2019, with an average annual percentage change of 5.4% (95% CI 4.1–6.7) over 14 years.…”
Section: Differences In Age and Gender‐specific Oral Cancer Incidence...mentioning
confidence: 58%
See 1 more Smart Citation
“…These findings have been corroborated by a recent study including data obtained from National Cancer Registry of Sri Lanka, as well as raw data possessed by National Cancer Control Programme for the period from 2005 to 2019. This study showed a rising trend in age standardized incidence rates, of oral cancer over the past two decades both in males and females 34 . Among males, the proportional increase in age standardized incidence rates rose from 9.8 to 19.1 per 100 000 population from 2005 to 2019, with an average annual percentage change of 5.4% (95% CI 4.1–6.7) over 14 years.…”
Section: Differences In Age and Gender‐specific Oral Cancer Incidence...mentioning
confidence: 58%
“…This study showed a rising trend in age standardized incidence rates, of oral cancer over the past two decades both in males and females. 34 Among males, the proportional increase in age standardized incidence rates rose from 9.8 to 19.1 per 100 000 population from 2005 to 2019, with an average annual percentage change of 5.4% (95% CI 4.1-6.7) over 14 years. The increase was less prominent among females which was 3.1% (95% CI 1.8-4.5), but an increase of age-standardized incidence rate was evident.…”
Section: Ifferen Ce S In Ag E and G Ender-s Pecifi C Or Al C An Cer I...mentioning
confidence: 98%
“…The age and gender profile of patients were similar to the previously reported. Squamous cell carcinoma of the oral cavity reported a higher prevalence in older age groups with a male predilection [6,8,9]. There were only two malignancies reported in patients under the age of 30 years, they were embryonal rhabdomyosarcoma and malignant myoepithelioma.…”
Section: Discussionmentioning
confidence: 98%
“…The number of new cases reported in the year 2019 was 2173 for males and 586 for female's island wide [5]. Further, a recent analysis reported an increasing trend in the age standardized incidence rates for lip and oral cavity cancers in Sri Lanka [6].…”
Section: Introductionmentioning
confidence: 99%